The Effects of Giving Moringa Leaf Tea for Increasing Hemoglobin Levels in Adolescent Girls - Aprilia, Dian; Amelia Kusumawardani, Paramitha; Cholifah, Siti (Universitas Islam Lamongan, 2024)
Anemia is a condition in which the number of red blood cells is insufficient to meet the physiological needs of the body due to the rapid growth rate combined with the depletion of iron stores and an inadequate diet. Based on data from the East Java Provincial Health Office in 2020 the prevalence of female adolescents in East Java who have anemia is 42%, including Sidoarjo Regency is ranked first in East Java with a prevalence of 32.9%. The purpose of this study was to determine the effect of giving moringa leaf tea on increasing hemoglobin levels in female adolescents. Pre Experimental research method with pretest-posttest design one group design . The population of this study were all young women at the Youth Posyandu in Putat Tanggulangin Village Sidoarjo and as many samples 19 young women (calculations attached) who met the inclusion and exclusion criteria . Research data were analyzed using data analysis Univariate was tested by paired t-test with a significant level of p.value <0.05 . Got results that there was a significant difference between hemoglobin levels before and after administration of moringa leaf tea (p<0.05).